Estimating Risk of Hematopoietic Acute Radiation Syndrome in Children. Issue 6 (December 2017) - Adams, Tim G.; Sumner, Louise E.; Casagrande, Rocco
Abstract : Abstract: Following a radiological terrorist attack or radiation accident, the general public may be exposed to radiation. Historically, modeling efforts have focused on radiation effects on a "reference man"—a 70‐kg, 180‐cm-tall, 20‐ to 30‐y-old male—which does not adequately reflect radiation hazard to special populations, particularly children. This work examines the radiosensitivity of children with respect to reference man to develop a set of parameters for modeling hematopoetic acute radiation syndrome in children. This analysis was performed using animal studies and the results verified using data from medical studies. Overall, the hematopoietic system in children is much more radiosensitive than that in adults, with the LD50 for children being 56% to 91% of the LD50 of adults, depending on age.